Analisis K-Means Clustering pada Sarana dan Perlengkapan Fasilitas KB di Provinsi Sumatera Barat Tahun 2024 - Fadilah, Salwa Hifa; Amalita, Nonong; Mutiya, Fenni Kurnia (Universitas PGRI Semarang, 2026)
The Family Planning Program (KB) is crucial for improving family welfare and controlling population growth. The program's success is largely determined by the availability of evenly distributed family planning facilities and equipment across all regions. This study aims to categorize districts and cities in West Sumatra Province based on the availability of these facilities and equipment to identify areas requiring priority intervention. K-means clustering was used with 10 types of family planning facilities and equipment as the variables. The results showed that two clusters were optimal, with the lowest DBI = 0,7239. The first cluster consisted of ten districts/cities with relatively low facility availability, and the second cluster included nine districts/cities with more adequate facilities.